The Influence Of Relationship Marketing And Price On Customer Satisfaction: A Case Study Of Alfamidi Super Masigi Parigi Outlet - Rahmat, Randi; Adam, Rosida P.; Bachri, Syamsul; Wanti, Sri (UNIVED Press, 2026)
This study aims to determine the effect of Relationship Marketing and Price on Customer Satisfaction at Alfamidi Super Masigi Parigi outlets. This study uses a quantitative approach with purposive sampling techniques on 84 respondents who have shopped at Alfamidi. Data collection was carried out through interviews and questionnaires, then analyzed using multiple linear regression with the help of the SPSS program. The results show that both Relationship Marketing and Price variables have a positive and significant effect on Customer Satisfaction, both partially and simultaneously. This indicates that the implementation of effective Relationship Marketing strategies and pricing policies that are in line with consumer purchasing power can increase customer satisfaction. Thus, good customer relationship management and appropriate pricing are important factors in building and maintaining customer satisfaction at Alfamidi Super Masigi Parigi.